Bending resistance of partially encased beams: experimental tests at elevated temperature - Piloto, P.A.G. (2015)
The bending performance of 27 Partially Encased Beams (PEB) is compared at different temperature levels using the four-point bending test setup. Tests consider only one composite cross section, two beam lengths and two different shear conditions for stirrups. The performance of PEB is also compared to bare steel I beams (IPE). Experimental measurements confirmed that temperature is not perfectly constant over the length of the heated beams, presenting strong gradients at extremities. Progressive damage of concrete occurred during experiments. The bending resistance of PEB at room temperature is much higher than bare steel beams and the bending stiffness is approximately 15% higher, being the post buckling deformation quite different. The reduction of the bending resistance of PEB at elevated temperature is not inversely proportional to the increase of the temperature. All tested beams attained lateral torsional buckling for deformed shape mode, with exception to those tested at 600 °C.